ANALISIS KESALAHAN BUKU PELAJARAN SUPER DEUTSCH KELAS XII(12) LEKTION 6 YANG BERJUDUL “LIEDER UND GEDICHTE” - Jihan Alfiana; Kezia Syalomitha; Putri Mayatantri (Cahaya Ilmu Bangsa Institute, 2025)
This study aims to find out what are the shortcomings and errors of the book. This Super Deutsch Textbook is considered good and feasible to use. In this student book there is a considerable amount of material discussion and competency training. This book is relevant to the applicable curriculum. It is said to be relevant because of the indicators analyzed, this book has presented well with the discovery of the diversity of values and up-to-date material. Based on its consistency, this book has been said to be consistent. Most of the indicators included in the consistency principle have been described in this book well. Likewise, the adequacy principle has also been described in this book. Thus, this textbook is suitable for use in the teaching and learning process by students to achieve learning objectives.